Human saliva exerts strong type-dependent effects on adenovirus infectivity - Sallard, Erwan; Zhang, Wenli; Chilakamarri, Nikita; Farzanehkari, Setareh; Seuthe, Inga Marte Charlott; Ehrhardt, Anja; Aydin, Malik (Frontiers in Immunology, 2025)
BackgroundThe development of mucosal adenovirus (Ad) vaccine vectors is considered one of the next frontiers to protect vulnerable patients from respiratory and gastrointestinal pathogens. An efficient delivery to or through the oral cavity necessitates a thorough understanding of Ad interactions with saliva for oral, buccal or sublingual vaccine delivery, which could additionally prove instrumental in the containment of natural Ad infections but remains unexplored. Therefore, we investigated the influence of saliva on Ad infectivity, emphasizing its intrinsic antiviral role against particular Ad types in various epithelial cell cultures.MethodsA saliva pool was created from healthy donors (n=16) and incubated with ChAdOx1 or human Ads from 20 different types prior to infection of human immortalized epithelial cells. All human Ads used were replication-competent and expressed a GLN cassette containing a green-fluorescent protein, nano-luciferase, and neomycin resistance. Loss-of-function experiments were conducted by immunoprecipitation or enzymatic digestion of specific saliva components to decipher related mechanisms.ResultsTemporal and inter-individual variability in saliva samples were observed, validating the use of a saliva pool to represent the population. Saliva strongly influenced Ad infectivity, in general through inhibiting species B types and enhancing species D and E Ads, that include the vaccine vector platforms Ad26 and ChAdOx1. Interestingly, Ad20 presented the highest infectivity enhancement, as well as superior to average salivary mucus crossing rates. Furthermore, saliva immunoglobulins and human neutrophil peptides marginally influenced the Ad infectivity, while sialic acid inhibited all tested Ad types.ConclusionSaliva may have a protective role against infection by certain types of Ads. This discovery highlights a potential limitation in the efficacy of next-generation oral Ad vaccine vectors. Consequently, our study underscores the importance of identifying and utilizing saliva-resistant Ad vectors to optimize Ad-based vaccination strategies.